National Breast Cancer Screening Programme, Singapore: Evaluation of participation and performance indicators. (December 2015) - Loy, En Yun; Molinar, Darko; Chow, Khuan Yew; Fock, Christine
Objective: To evaluate participation rates and performance indicators in the National Breast Cancer Screening Programme, BreastScreen Singapore (BSS). Methods: Data on women aged 40-69 screened in the period 2002-2009 was obtained from BSS and from the Singapore Cancer Registry. Participation rates and performance indicators (including screen detection rates, small tumour detection rates, recall rates, accuracy and interval cancer rates) were examined. Results: BSS participation rate has remained above 10% since 2005. Based on health surveys, national mammography rates have increased from 29.7% before BSS to 39.6% in 2010 after BSS. Performance indicators, with the exception of recall rates, specificity, and interval cancer rate (for first screen), generally improved from 2002-2006 to 2007-2009 and are comparable with organized breast screening programmes in other developed countries. Conclusion: BSS breast cancer screening coverage and rescreen rates in Singapore could be improved. Mechanisms to monitor recall rates are in place, and training opportunities are provided to aid the professional development of radiologists.